2014
DOI: 10.1021/ic402909t
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Selenite from Water Using a Synthetic Dithiolate: An Experimental and Quantum Chemical Investigation

Abstract: Combination of the dithiol N,N'-bis(2-mercaptoethyl)isophthalamide, abbreviated as BDTH2 and as 1, with excess H2SeO3 in aqueous acidic (pH ≈ 1) conditions resulted in precipitation of BDT(S-Se-S) (6), with a (77)Se NMR chemical shift of δ = 675 ppm, and oxidized BDT. When the reaction is conducted under basic conditions Se(IV) is reduced to red Se(0) and oxidized 1. No reaction takes place between 1 and selenate (Se(VI)) under acidic or basic conditions. Compound 6 is stable in air but decomposes to red Se(0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…(1) and (2) [24]. Selenite is a softer base than selenate [25] and thus has smaller resistance to electron transfer and is more reactive with Fe 0 [26].…”
Section: Effect Of Initial Se(vi) Concentrationsmentioning
confidence: 99%
“…(1) and (2) [24]. Selenite is a softer base than selenate [25] and thus has smaller resistance to electron transfer and is more reactive with Fe 0 [26].…”
Section: Effect Of Initial Se(vi) Concentrationsmentioning
confidence: 99%
“…The low barriers for these two steps are consistent with experimental rates observed by Kice. 78 Recently, Burriss et al 81 have suggested that a cyclic compound similar to 7 could rearrange to shift the oxygen to a sulfur center or transfer the oxygen between a sulfur and selenium center (Se−O−S). The related species MeSSe-O-SMe is 3.3 kcal/mol less stable than 7 suggesting that the release of ring strain may be important to Burriss's species.…”
Section: ■ Results and Discussionmentioning
confidence: 99%